Kualitas Hasil Tanaman Krisan (Crhysanthemum) pada Penambahan Cahaya Lampu LED Merah secara Siklik - Pande Putu Indra Yoginugraha; I Made Anom Sutrisna Wijaya; I Made Nada (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This study aimed to determine the cyclic time that could give the best quality of the results of chrysanthemum. The treatment of this research was additional LED red light in the cyclic manner with different cycle time. The collected data were analyzed by descriptive analysis and the variables observed were grouped into 2 groups such as : production and quality of chrysanthemum. The result showed that the highest production and the best quality of chrysanthemum were obtained on the treatment of additional LED red light with five cycles. The production of the chrysanthemum was 85.83 cm, the amount of flowers was 23.67 of flowers, and in a quality manner of flower area was 52,96 cm2. The more the cycles that had given on the addition of LED red light, the better the results of production and quality of chrysanthemum.